Fungicidal and bactericidal activity of alkyl-substituting polyetherguanidines - M. Ya. Vortman; Yu. B. Pysmenna; A. V. Rudenko; V. V. Tretyak; V. N. Lemeshko; V. V. Shevchenko (Біологічні студії, 2020)
Background. Polyhexamethylene guanidines are widely used as biocides and disinfectants due to the wide range of their antimicrobial activity against Gram-positive and Gram-negative bacteria, viruses, fungi, and molds. The mechanism of biocidal action of polyguanidines is similar to that of quaternary ammonium compounds and has a membrane toxic nature. The advantages of polyhexamethylguanidines salts include their moderate toxicity and a lack of cumulative action against living organisms. The convenience of such polymeric biocides lies in their high water solubility and in the absence of volatility, which allows disinfectant work to be carried out in the presence of people. It is known that the introduction of alkyl radicals into the polymer chain leads to an increase in the bactericidal and fungicidal action of the obtained compounds. In order to enhance these properties, it seems promising to obtain polyetherguanidines with alkyl radicals in their structure. The aim of this work was to study the fungicidal and bactericidal activity of synthesized alkyl-substituted polyetherguanidinium iodides against a number of bacteria and microscopic fungi. Methods. Bacteria were grown on the meat-peptone agar for 48 hours at 28±2 °C. Test cultures of micromycetes were cultured on agar beer wort (6 ° B), incubated for 14 days at 28±2 °C. Antimicrobial and fungicidal activities of the newly synthesized alkyl-substituting polyetherguanidines were determined by the standard disco-diffusion method. Results. The synthesis of polyetherguanidinium iodide is carried out in four stages. The first stage is the synthesis of a guanidine-containing oligoether with terminal guanidine moieties by the reaction between aromatic oligoepoxide and guanidine. The second stage is the synthesis of polyetherguanidinium chloride by the reaction between guanidinium-containing oligoether with terminal guanidine fragments and oligooxyethylenediamine of different molecular weight. In the third stage, the obtained polyetherguanidinium chloride is converted from the salt form to the base form by the reaction with an equivalent amount of alkali in ethanol. In the fourth stage, the basic polyetherguanidine is reacted with methyl iodide at a molar ratio of polyetherguanidine: methyl iodide components of 1:2. The bactericidal and fungicidal activities of alkyl-containing polyetherguanidinium iodides against various heterotrophic bacteria and microscopic fungi has been shown. It was found that polyetherguanidinium iodides at a concentration of 1–3% inhibited the growth of Gram-negative (Escherichia coli 475, Klebsiella pneumonia 479) and Gram-positive (Staphylococcus aureus 451) bacteria. The obtained alkyl-containing polyetherguanidinium iodides at a concentration of 1% for 14 days showed fungicidal activity in almost all studied isolates. With an increasing length of the oligoethylene oxide component, the obtained polymers with n = 10 and 50 did not show a fungicidal effect against Aspergillus niger, and the polymer with n = 50 – against the micromycete Aspergillus versicolor. If we determine the fungicidal effect as a whole, the polymer with n = 6 had the highest activity against all studied isolates after 14 days, while the fungicidal effect of polymers with n = 10 and n = 50 tends to decrease. All synthesized alkyl-containing polyetherguanidinium iodides showed the highest activity against such microscopic fungi as Cladosporium cladosporioides, Acremonium strictum, Alternaria alternate, Cladosporium sphaerospermum, Paecilomyces variotii, Stachybotrys chartarum. Also noteworthy is the selective effect of the obtained polymers on individual isolates. Conclusions. The obtained polyetherguanidinium iodides of different molecular weight at a concentration of 1–3% showed bactericidal activity against Staphylococcus aureus 451, Escherichia coli 475, Klebsiella pneumoniae 479 and fungicidal effect against all fungi studied by us and can be used as disinfectants for indoor treatment.